Authority figures : rhetoric and experience in John Locke's political thought - Shanks, Torrey (University Park, Pennsylvania : The Pennsylvania State University Press, 2014)
"Examines the place of rhetoric in John Locke's political and philosophical thought. Traces the close ties between rhetoric and experience as they form the basis for a theory and practice of judgment at the center of his work"--Provided by publisher.
Rhetoric and situated political critique -- The claim to experience -- Material words and sensible judgment -- Feminine figures and the rhetoric of critique -- The matter of consent -- Conclusion : critical temporalities.
Includes bibliographical references (pages 137-143) and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2015. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Locke, John, -- 1632-1704 -- Views on political science; Political science; Rhetoric -- Political aspects; Electronic books